1996
DOI: 10.1002/(sici)1097-0142(19960301)77:5<858::aid-cncr8>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of vascular endothelial growth factor expression in gastric carcinoma

Abstract: The expression of VEGF may be a good prognostic indicator for patients with gastric carcinoma and may also be useful as a predictor of the mode of recurrence in patients with gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
299
4
17

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 563 publications
(343 citation statements)
references
References 15 publications
17
299
4
17
Order By: Relevance
“…Moreover, tissue VEGF concentration measured by ELISA was also an independent prognostic factor for patients with soft tissue sarcomas. Similar results have been reported in studies on several cancers including human colon cancer (Takahashi et al, 1995), brain tumour (Takano et al, 1996), and gastric cancer (Maeda et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, tissue VEGF concentration measured by ELISA was also an independent prognostic factor for patients with soft tissue sarcomas. Similar results have been reported in studies on several cancers including human colon cancer (Takahashi et al, 1995), brain tumour (Takano et al, 1996), and gastric cancer (Maeda et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…It is now thought that expression of the tumour cell derived angiogenic factors is specific to each tumour and dependent on the process of tumour growth and spreading. Several studies have noted that the level of expression of VEGF, which is a strong angiogenic factor, correlates with neovascularity and with tumour progression in human colon cancer (Takahashi et al, 1995), human brain tumour (Takano et al, 1996), human breast cancer (Maeda et al, 1996), and several experimental tumour models (Miller et al, 1994;Zhang et al, 1995;Claffey et al, 1996). VEGF secreted from tumours may contribute to tumour growth, invasion and metastasis not only via an autocrine pathway to tumour cells, but via a paracrine pathway to surrounding microvessels (Takahashi et al, 1995).…”
mentioning
confidence: 99%
“…It is mitogenic and angiogenic for endothelial cells, and it can also increase vascular permeability. A number of tumour cells in humans have been seen to express higher levels of VEGF mRNA compared to normal tissue (Brown et al, 1993;Plate et al, 1993;Abu-Jawdeh et al, 1996;Yoshiji et al, 1996), suggesting an association of VEGF with a malignant phenotype; furthermore, an elevated VEGF expression has also been correlated to a worse prognosis in cancers such as gastric (Maeda et al, 1996;Takahashi et al, 1996), colonic (Takahashi et al, 1995) and lung carcinomas (Mattern et al, 1995;Ohta et al, 1996;Fontanini et al, 1997bFontanini et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 VEGF is produced in a great variety of cells and is expressed in tumors of many tissues, including lung, breast, stomach, colon, thyroid, kidney, bladder, ovary, and pituitary. [13][14][15][16][17][18][19][20][21] VEGF also has been identified in human craniopharyngiomas, and it has been suggested that cystic foci in these tumors are related to the degree of VEGF expression. 22 To assess directly whether VEGF in craniopharyngiomas is associated with angiogenesis and tumor behavior, we compared the expression pattern of VEGF with both microvessel density (MVD) and clinicopathologic features in 32 adult patients with craniopharyngiomas of both histologic types.…”
mentioning
confidence: 99%